Investigating acrylamide mitigation by potential probiotics Bifidobacterium breve and Lactiplantibacillus plantarum: Optimization, in vitro gastrointestinal conditions, and mechanism. (15th June 2022) - Albedwawi, Amal S.; Al Sakkaf, Reem; Osaili, Tareq M.; Yusuf, Ahmed; Olaimat, Amin; Liu, Shao-Quan; Palmisano, Giovanni; Shah, Nagendra P.; Ayyash, Mutamed M.
Abstract: This paper investigated the ability of lactic acid bacteria (LAB) and Bifidobacterium to remove acrylamide (AA). The mechanism(s) of the AA removal was examined by various microscopic techniques. After screening 40 isolates, Bifidobacterium breve and Lactiplantibacillus plantarum exhibited higher acrylamide (AA) reduction by 35% and 36%, respectively. pH (4.5–6.5), incubation temperature (32–42 °C), incubation time (14–22 h), and NaCl (0–3 g/100 g) were employed using Box-Behnken design (BBD) to investigate the AA removal. As a result, the AA removal ranged from 47.7 to 65.0% for B. breve and 5.8%–8.0% for Lb. plantarum . Under the in vitro gastrointestinal conditions, B. breve removed up to 41.2% of acrylamide while Lb. plantarum reduced around 53.5% of acrylamide. In addition, both strains tolerated low pH levels. TEM images showed that cells of both bacteria increased after culturing with acrylamide. Elements analysis of Lb. plantarum and the most dominant elements are C, N, and O with atomic % of 41.95, 17.63, and 31.66, respectively. FTIR exhibited that CO, C–O, and N–H were main functional groups associated with AA adsorption in Lb. plantarum and B. breve . The zeta potential values of B. breve and Lb. plantarum are −15.47 and −25.87 mV, respectively. Highlights: Acrylamide was mitigated by potential probiotic bacteria. Acrylamide was removed during the in vitro digestion by the potential probiotics. pH played major role in removing acrylamide by LAB and bifidobacteria. Results exhibited that acrylamide adhere to cell wall of the potential probiotics.